Proposta de gestão pedagógica para o ensino de língua portuguesa por meio de dispositivos móveis - Bitencourt, Dariane de Castro (2019)
The contemporary and technological scenario demands new skills from its users for reading, comprehension and production of digital and multimodal texts disseminated in society (ROJO 2015; RIBEIRO 2016), mainly through mobile devices. In the students' daily life, the cell phone is one of the most used technologies, however, in the school context this tool ends up being seen as an instrument of distraction in the classes, being still little used pedagogically. Therefore, it is essential to research alternatives that can contribute to minimize these difficulties in practice, regarding the inclusion of this technology in the classroom, since it is essential to adapt the teaching practice to these demands, strengthening students' engagement and learning. using technologies familiar to you. Therefore, this research, conducted with high school students from a public school in Alegrete, RS, presents a pedagogical management proposal that explores the use of mobile phones, as a technological tool, capable of assisting in learning and working with genders. discursive and multimodal lessons in Portuguese language classes. This dissertation proposed in the Postgraduate Program in Networked Educational Technologies, in the research line Management of Networked Educational Technologies, reports an exploratory research with a qualitative approach and uses action research to investigate, elaborate, describe and apply as a method. practical activities that may be mediated through mobile devices. For this, we tested the activities developed with different audiences, in order to validate the management proposal,seeking further development of the reading and socio-communicative skills of the students. As a result, the data show that the proposed activities fostered pedagogical practices with mobile devices and allowed students to appropriate understanding of what discursive and multimodal genres are, as participants are able to demonstrate such knowledge in their productions, as well as when evaluating the applied experience. Thus, we emphasize that the inclusion of mobile phones as technology in the classroom makes the teaching and more challenging, motivating, and engaging learning, and allows students to feel more motivated and confident when using this technology in class. In summary, the management proposal suggests steps, described in this study, that guide the pedagogical practice with mobile devices, through the application of technological challenges, via WhatsApp and Edmodo. In addition, we have prepared an ebook for teachers with proposed activities, resulting from this research.